Factors determining susceptibility to temporary threshold shift in humans: insights from concert attendance - Murray, Carlyn; Guest, Hannah; Prendergast, Garreth; Munro, Kevin; Millman, Rebecca; Roberts, Stephen A.; Kluk, Karolina; Plack, Christopher J. (Frontiers in Audiology and Otology, 2025)
Noise exposure can induce temporary threshold shifts (TTS), typically assessed using pure-tone audiometry (PTA). The magnitude of TTS is influenced by noise attributes such as duration and intensity, but likely also by a number of personal factors influencing individual susceptibility. Most research on such factors has relied on experimentally induced TTS, which enables controlled exposures but cannot generate substantial TTS without raising ethical concerns. This study explored an alternative paradigm, measuring TTS in 51 young adults immediately after attending a noisy concert. Potential predictors included self-reported noise exposure in the weeks preceding the event, hypothesized to have a “conditioning” effect that mitigates TTS, as well as sex and skin tone, since female sex hormones and higher melanin levels may have otoprotective effects. Temporary auditory shifts were measured primarily using PTA at 3–6 kHz, with supplementary assessments via distortion-product otoacoustic emissions (DPOAEs), extended high-frequency (EHF) audiometry, and self-reported tinnitus. Pre-registered hypotheses predicted reduced TTS with higher prior noise exposure, female sex, and darker skin tones. Results revealed robust shifts in PTA, modest shifts in DPOAEs, and increased tinnitus reports, but no shifts in EHF measures. Regression analyses showed non-significant trends aligning with the conditioning noise and sex hypotheses, but not skin tone. The pre-and-post-concert paradigm proved effective, with high participant engagement and compliance during late-night testing. This methodology shows promise for future studies on TTS susceptibility, and recommendations are provided to refine its implementation.